Transcriptomic Profiling Provides Molecular Insights Into Hydrogen Peroxide-Enhanced Arabidopsis Growth and Its Salt Tolerance - Zhang, Qikun; Dai, Xiuru; Wang, Huanpeng; Wang, Fanhua; Tang, Dongxue; Jiang, Chunyun; Zhang, Xiaoyan; Guo, Wenjing; Lei, Yuanyuan; Ma, Changle; Zhang, Hui; Li, Pinghua; et al. (Frontiers in Plant Science, 2022)
Salt stress is an important environmental factor limiting plant growth and crop production. Plant adaptation to salt stress can be improved by chemical pretreatment. This study aims to identify whether hydrogen peroxide (H2O2) pretreatment of seedlings affects the stress tolerance of Arabidopsis thaliana seedlings. The results show that pretreatment with H2O2 at appropriate concentrations enhances the salt tolerance ability of Arabidopsis seedlings, as revealed by lower Na+ levels, greater K+ levels, and improved K+/Na+ ratios in leaves. Furthermore, H2O2 pretreatment improves the membrane properties by reducing the relative membrane permeability (RMP) and malonaldehyde (MDA) content in addition to improving the activities of antioxidant enzymes, including SOD, and GPX. Our transcription data show that exogenous H2O2 pretreatment leads to the induced expression of cell cycle, redox regulation, and cell wall organization-related genes in Arabidopsis, which may accelerate cell proliferation, enhance tolerance to osmotic stress, maintain the redox balance, and remodel the cell walls of plants in subsequent high-salt environments.